Children's dietary data from Food Africa Project conducted in the communes of Bopa and Houeyogbe, Benin - Bodjrenou, Fifali Sam Ulrich; Termote, Celine; Koukou, Elie; Amoussa Hounkpatin, Waliou; Mitchodigni, Medeme Irene; Ntandou Bouzitou, Gervais Deleuze (2024)
The purpose of this study is to assess Infant and young children's feeding practices and explore how they meet energy and nutrient intake requirements. Also, this study aims to explore the dietary contribution of local biodiversity to children's diets in the communes of Bopa and Houeyogbe, Benin.